ANALGESIC PHARMACOTHERAPY IN DYSMENORRHEA AND THE RISK OF DEVELOPING CHRONIC MIGRAINE - Karolina Wojdat-Krupa; Weronika Ossowska; Filip Lachowski; Karol Sikora; Julia Dolinkiewicz; Martyna Wasyluk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Dysmenorrhea, particularly primary dysmenorrhea, is a common gynecological condition characterized by cyclical and often severe pain, typically managed with analgesics such as NSAIDs, acetaminophen, and opioids. Habitual, suboptimal, or excessive use of these medications may facilitate the transformation of episodic headaches into chronic forms through central sensitization and receptor-level changes in the central nervous system. Despite widespread pharmacotherapy, comprehensive synthesis regarding its role in chronic migraine development is lacking. This review systematically summarizes data from cohort, case-control, and interventional studies to evaluate the relationship between dysmenorrhea pharmacotherapy and chronic migraine risk. The study examines whether medication type, frequency of use, and patient-related factors—including age at dysmenorrhea onset, pain severity, comorbid psychiatric disorders, and use of migraine prophylactic agents—modulate this risk. Results: Medication overuse headache (MOH) arises from excessive use of acute headache medications in patients with primary headache disorders, most commonly migraine. Opioids, butalbital-containing analgesics, acetaminophen–aspirin–caffeine combinations, and triptans confer the highest risk of chronification, while NSAIDs carry moderate risk and hormonal therapies may reduce pain frequency and intensity, potentially decreasing the need for frequent analgesic use. Frequent acute medication use (NSAIDs or acetaminophen ≥15 days/month, opioids/triptans ≥10 days/month), early dysmenorrhea onset, severe pain, and comorbid psychiatric conditions significantly increase MOH and chronic migraine risk. Implementation of prophylactic therapies and patient education can reduce reliance on acute medications and mitigate headache chronification. Conclusion: Analgesic use in dysmenorrhea carries a risk of chronic migraine development, particularly with high-frequency or high-risk medications. Hormonal therapies, prophylactic strategies, individualized treatment, and monitoring of acute medication use are critical to minimize MOH and optimize long-term outcomes.